Revealing the influence of Mo addition on interphase precipitation in Ti-bearing low carbon steels. (15th January 2022) - Dong, Haokai; Chen, Hao; Riyahi khorasgani, Ahmadreza; Zhang, Boning; Zhang, Yongjie; Wang, Zhenqiang; Zhou, Xiaosheng; Wang, Wei; Wang, Huanrong; Li, Tong; Yang, Zhigang; van der Zwaag, Sybrand
Graphical abstract: Image, graphical abstract Abstract: Mo is widely used as an effective microalloying element to improve mechanical performance of interphase precipitation steels, but the precise role of Mo in interphase precipitation behavior is not fully understood. In this contribution, interphase precipitation behavior in a series of Ti-Mo-bearing low carbon steels is systematically studied, and the role of Mo in interphase precipitates and its coarsening behavior is revisited. It is found that (Ti, Mo)C precipitates instead of TiC are formed in the Mo-containing alloys, and the average site fraction of Mo in (Ti, Mo)C is almost independent of the bulk Mo content. Moreover, the number density of interphase precipitates can be substantially enhanced by a minor addition of Mo, albeit it does not further rise with increasing the bulk Mo content. This is because the Mo fraction in (Ti, Mo)C rather than the bulk Mo content governs the driving force for precipitation nucleation and the interfacial energy of the (Ti, Mo)C/α and (Ti, Mo)C/γ interfaces. In addition to the reduced interfacial energy, decrease of Ti trans-interface diffusivity has been identified as another key reason for the enhanced carbide coarsening resistance in Mo-containing alloys.